Work as an external quantum observable and an operational quantum work fluctuation theorem - Konstantin Beyer; Kimmo Luoma; Walter T. Strunz (Physical Review Research, 2020)
We propose a definition of externally measurable quantum work in driven systems. Work is given as a quantum observable on a control device which is forcing the system and can be determined without knowledge of the system Hamiltonian H[over ̂]_{S}. We argue that quantum work fluctuation theorems which rely on the knowledge of H[over ̂]_{S} are of little practical relevance, contrary to their classical counterparts. Using our framework, we derive a fluctuation theorem which is operationally accessible and could in principle be implemented in experiments to determine bounds on free energy differences of unknown systems.